1990
DOI: 10.1099/00221287-136-10-2013
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of recombinant fragments of the major outer-membrane protein of Chlamydia trachomatis: their potential as subunit vaccines

Abstract: Recombinant fragments of the major outer-membrane protein (MOMP) of C h y & ~~~h o m u t i s ,expressed at higb levels in Esckrichiiz coli, were isolated and purified. Antisera to the recombinant proteins reacted preferentially with overlapping synthetic peptides covering the immunoaccessible variable segments of MOMP.These sera also reacted in a species-specific manner with the surface of intact infectious elementary bodies, and in a Chlamydia genus-specific manner in assays using denatured or bound chlamydia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The MOMP, which is found in both EBs and RBs, is thought to act as a porin (Bavoil etal., 1984) and has a role in the attachment and uptake of EBs by host cells. It is also recognized as an exposed surface molecule possessing infection-neutralizing epitopes (Collett e t al., 1989 ;Zhang e t al., 1989 ;Conlan et al, 1989 ;Conlan et al, 1990;Peterson e t al., 1990). Polyacrylamide gel analysis of C. tracbomatis proteins has shown that the 60 kDa CrP occurs as a singlet in the trachoma biovar and as a 60/62 kDa doublet in the LGV biovar (Batteiger e t d., 1985).…”
Section: Members Of the Genusmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOMP, which is found in both EBs and RBs, is thought to act as a porin (Bavoil etal., 1984) and has a role in the attachment and uptake of EBs by host cells. It is also recognized as an exposed surface molecule possessing infection-neutralizing epitopes (Collett e t al., 1989 ;Zhang e t al., 1989 ;Conlan et al, 1989 ;Conlan et al, 1990;Peterson e t al., 1990). Polyacrylamide gel analysis of C. tracbomatis proteins has shown that the 60 kDa CrP occurs as a singlet in the trachoma biovar and as a 60/62 kDa doublet in the LGV biovar (Batteiger e t d., 1985).…”
Section: Members Of the Genusmentioning
confidence: 99%
“…Purified chlamydiai preparations from each of the three species that were a mixture of EB with intermediate bodies and a few reticulate bodies were used in these studies. An antiserum raised to C. trachomatis recombinant MOMP expressed in E. coli as insoluble cytoplasmic inclusion bodies (Conlan et al, 1990) was used as a positive control to demonstrate the technique. The results indicated that none of the antisera to the various 60 kDa CrPs showed any surface labelling in either heterologous or homologous combinations.…”
Section: Surface Accessibility Of 60 Kda Crp Epitopesmentioning
confidence: 99%
“…Prior vaccination experiments conducted in animal models of either C. trachomatis or C. psittaci infections have used purified inactivated elementary bodies (EB), purified MOMP or recombinant MOMP (rMOMP) expressed by Escherichia coli, and subfraction or subunit preparations of MOMP (2,5,9,12,17,19). However, these methods had substantial limitations that would be overcome if the outer membrane protein 1 (omp1) gene encoding the MOMP could be expressed in the host cell itself.…”
mentioning
confidence: 99%
“…These studies were based on the simple notion that neutralizing antibodies to surface-exposed antigenic sites on the organism constituted immunity. Great efforts were devoted to investigating antibody responses following immunization or infection and on localization and characterization of neutralization epitope(s) on chlamydial antigens (5)(6)(7)(8)(9)(10)(11)(12)(13). The data that supported the notion of antibodymediated immunity arose from observations that serum and monoclonal antibodies specific for C trachomatis are able to neutralize the organism in tissue culture (14,15).…”
mentioning
confidence: 99%